Proceedings of the 21st ACM Conference on Hypertext and Hypermedia 2010
DOI: 10.1145/1810617.1810632
|View full text |Cite
|
Sign up to set email alerts
|

The influence of adaptation on hypertext structures and navigation

Abstract: In adaptive hypertexts the user is guided in two ways: through the existence of links and through link annotation or hiding. Link structures have been investigated, starting with Botafogo et al, and the effect of link annotation has been studied, for instance by Brusilovsky et al. This paper studies the combined effect of link structure and annotation/hiding on the navigation patterns of users. It defines empirical hubs and studies their correlation with hubs as defined by Kleinberg without considering adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
0
5
2
Order By: Relevance
“…The CT infection rate of 23.9% found in this high-risk population was higher than in other Brazilian studies with pregnant women from 6 important cities [26], with adolescents [5,27], as well as in studies carried out in several developed countries [2,4]. Aiming at women with a high genital infection risk, however, a previous study from the same region also revealed a CT prevalence of 25.7% in pregnant women attending an obstetrics unit specialized in genital tract infection [6]. The high rate of C. trachomatis in this study can be explained by the design of this study.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…The CT infection rate of 23.9% found in this high-risk population was higher than in other Brazilian studies with pregnant women from 6 important cities [26], with adolescents [5,27], as well as in studies carried out in several developed countries [2,4]. Aiming at women with a high genital infection risk, however, a previous study from the same region also revealed a CT prevalence of 25.7% in pregnant women attending an obstetrics unit specialized in genital tract infection [6]. The high rate of C. trachomatis in this study can be explained by the design of this study.…”
Section: Discussioncontrasting
confidence: 61%
“…Unexpectedly, the BV rate in the present study was not only lower than in pregnant women attending a Primary Care Service [28] or an outpatient service specialized in infections in Obstetrics [6] in the same region, but was also lower than in non-pregnant Brazilian [29] and North-American women [24]. This low Total of patients may vary among the categories as some of the data was unavailable prevalence of bacterial vaginosis could partly be explained by the consideration that combined infection of vaginal candidosis and BV was analyzed separately from BV without co-infection.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations